Ventricular pacing and myocardial function in patient with congenital heart block. (24th August 2021) - Rangavajla, Gautam; Mulukutla, Suresh; Thoma, Floyd; Kancharla, Krishna; Bhonsale, Aditya; Estes, N. A. Mark; Jain, Sandeep K.; Saba, Samir
Abstract: Introduction: Pacing‐induced cardiomyopathy (PICM) is a potential complication of chronic right ventricular (RV) pacing, but its characterization in adult patients is often complicated by pre‐existing cardiomyopathy. This study investigated the incidence of PICM in patients with congenital heart block (cHB) who have conduction disease from birth without confounding pre‐existing cardiac conditions. Methods and Results: This retrospective cohort analysis included 42 patients with cHB and baseline left ventricular ejection fraction (LVEF) ≥50%. Kaplan–Meier analysis was used to assess freedom from cardiomyopathy (defined as LVEF <50%) between paced and nonpaced patients. Patients were 26 ± 3 years old at first presentation, 64% were women and baseline LVEF was 60.0 ± 0.2%. Median follow‐up from birth was 35 (interquartile range [IQR]: 20–42) years with a median of 6.7 years (IQR: 3.6–9.2) at our institution. Thirty‐two patients received pacing at mean age 21 ± 3 years. Patients receiving a pacemaker (PM) were significantly more likely to develop a cardiomyopathy ( p = .021) and no patient developed a cardiomyopathy in the absence of a PM. Four patients who developed a new cardiomyopathy were upgraded to biventricular pacing, leading to stabilization or improvement of LVEF. Conclusion: In a relatively young and healthy cHB cohort, RV pacing is associated with a higher risk of developing a cardiomyopathy. These data confirm the deleterious effects of RV pacing on myocardial function in patients without pre‐existing structural cardiac disease and has clinical implications to the management of patients with cHB.